Statistics for an international economist - Khomyak, Maria (Lesya Ukrainka Volyn National University, 2025)
Annotation: The manual "Statistics for an International Economist" is designed for undergraduate students in Specialty 292 "International Economic Relations". It introduces the basics of statistical methods and their applications in international economic practice. The content includes lectures on core statistical concepts, data analysis, probability, sampling, and hypothesis testing, as well as practical tasks that develop skills in data processing, visualization, and interpretation. The manual can be used for both classroom study and independent learning.
Keywords: STATISTICS; 31:33(07)